In-situ remediation of arsenic-contaminated sites - Bundschuh, Jochen; Holländer, Hartmut M.; Ma, Lena Qiying (Arsenic in the environment,, 2014)
"Providing an introduction, scientific background, case studies and future perspectives of technologies for soils, soil water and groundwater at contaminated sites. Case studies present especially arsenate and arsenite, but also organic arsenic compounds. The work covers geochemical, microbiological and plant ecological solutions for arsenic remediation. Part I: Introduction, Background and Remediation Technologies; Part II: Case Studies: Soils; Geogenic, Mining-Related and Anthropogenic Contaminated Sites; Technical, Ecological and Economical Sustainability of In-Situ Remediation; Modeling."--